Keberkesanan program bandar selamat dari persepsi pelancong Singapura (Kajian Kes: Bandaraya Johor Bahru) - Anuar, Ahmad Nazrin Aris (2008)
In recent years, safety becomes one of prominent issues amongst tourist in the urban tourism. This issue has led to the implementation of Safe City Programme in Malaysia as to strengthening the urban tourism safety. In fact crimes rates appear to be common indicator among the urban tourist for measuring the urban safety. Therefore a case study has been carried out in Bandaraya Johor Bahru through Majlis Bandaraya Johor Bahru (MBJB) as a local authority which has applied Safe City Programme since 22nd November 2004 to intend more safety to the tourist. Singaporean tourists had preferred as the respondent to this study because they are a major tourists to Bandaraya Johor Bahru. When Safe City Programme had implemented in Bandaraya Johor Bahru, many respondents presume that a crime prevention step in Safe City Programme is an important steps to ensure the level of touristâ€™s safety. But from the effectiveness, many respondents had preferred â€œaverageâ€? to presume a crime prevention step in Bandaraya Johor Bahru. In light of findings, it is recommended that the tourism industry and law enforcement agencies co-ordinate to improve crime prevention step in Safe City Programme in Bandaraya Johor Bahru.